RELATIONSHIP BETWEEN LENGTH OF SERVICE AND THE WORKINGS OF FREIGHT LIFT WITH LOW BACK PAIN IN THE CARRYING TRADE IN 2 TRADITIONAL MARKETS BERINGHARJO YOGYAKARTA - Asda, Patria; Sumekar, Ariana; Ngongo, Yosef Fabianus (Jurnal Kesehatan Masyarakat, 2013)
ABSTRACT Lift freight work is risky work on the incidence of lower back pain. Back painis pain that occurs in the back and may spread to the legs, especially theback and outer Based on preliminary studies, the workers carry onBeringharjo, have worked long enough and did not work ergonomically.Based on these problems, the research was conducted